Bone strength analyzer and monitoring device for lower limb external fixation - Devin Babu; Waheb A. Jabbar; Muhammad Hisyam Rosle; Noorazliza Sulaiman; Mohd Amir Shahlan Mohd Aspar; Abdul Nasir (Institute of Advanced Engineering and Science, 2026)
The procedure for external fixator removal in lower limb fractures is typically based on radiographic data, subjects’ patients to ionising radiation, and provides minimal real-time information about the healing process. This project suggests a sensor-based Internet-of-Things apparatus, which will measure bone strength during the recuperating process based on load cells, HX711 amplifiers, and a Wemos ESP8266 microcontroller. The system provides real-time feedback in the form of LED indicators and a buzzer, whereas remote monitoring is supported by the Blynk dashboard. Measurement accuracy of over 90% was carried out as per the experimental validation conducted under the simulation of various loads (3-9 kg) and with clear stage indicators of critical, partial, and full recovery. The device offers continuous monitoring and objective bone healing evaluation with no radiation in comparison to conventional imaging. The limitation of the study is the limited range of loads in prototype testing, which could affect accuracy in particular situations. However, the results represent the possible clinical relevance of introducing real-time biomechanical surveillance into the process of fracture treatment, hence contributing to safer rehabilitation and more reasonable decisions related to the fixator removal.